Kontak Kebudayaan Arab, Yunani dan Persia - Harahap, Rendi Syahrinal (Yayasan Albahriah Jamiah Indonesia, 2025)
Cultural contact between Arabs, Greeks, and Persians is one of the important phenomena in the history of world civilization, especially during the golden age of Islam (8th to 13th centuries AD). This interaction not only involved political and economic exchanges, but also included profound intellectual and cultural dimensions. The background of this study is based on the need to understand how the process of contact and acculturation shaped the development of science, philosophy, art, and religion in the classical Islamic world. The formulation of the problem in this study is what form of cultural contact between Arabs, Greeks, and Persians, and to what extent each culture contributed to Islamic civilization. This study aims to analyze the forms of cultural interaction and their impact on the development of Islamic culture. The method used is a literature study with a historical-analytical approach to primary and secondary sources. The results of the study show that Greek culture contributed greatly to the fields of philosophy and science through the process of translating classical works into Arabic, while Persian culture had a major influence on government administration, literature, and art. The conclusion of this study is that the interaction between the three cultures formed a strong foundation for the birth of a cosmopolitan and transnational Islamic civilization. This study emphasizes the importance of intercultural dialogue in forming an advanced and inclusive civilization.